EVALUASI SOFTWARE CAD UNTUK MAHASISWA TEKNIK SIPIL DAN ARSITEKTUR SEBAGAI PEMBUATAN GAMBAR KERJA - Dody Irnawan; Silvia Yulita Ratih (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2021)
The development of science is increasingly rapid, one of which is digital technology as a drawing tool that continues to grow. Building Construction Structure is one of the courses in the Architecture Study Program, at the Faculty of Civil Engineering and Planning, University of Surakarta, the use of computer technology has indeed been applied to one of the courses, namely the Digital Architecture course which teaches about the basics of using the AutoCAD program. with its application to the manufacture of construction drawings, this study tries to make a comparison between AutoCAD and other software that is devoted to the field of architecture and civil engineering or specifically to the construction sector. The ArchiCAD software provides convenience in the form of tools that are already in the form of technical functions on structural elements and building architecture. Students really need to be introduced to ArchiCAD to support the creativity of ideas, designs and complete working drawings that are sustainable so that they are time efficient and support other courses.